Higher Education Access and Outcomes for the 2008 South African National Matric Cohort - Hendrik van Broekhuizen; Servaas van der Berg; Heleen Hofmeyr (Institute for the Study of Labor (IZA), 2016)
This study uses a unique dataset to investigate university access, throughput, and dropout for the 2008 South African national matric cohort. The findings show that university access in South Africa is limited, even among learners who perform relatively well in matric. In addition, those who do gain access to university often take a long time to complete their studies, with many never completing at all. As a result, only a select minority of matric learners manage to obtain university qualifications. Significant inequalities in university outcomes between race groups and across geographical space also remain evident. However, the results from the analysis suggests that observed patterns of university access and university success are strongly influenced by school results. The weak school system has a major influence on who reaches matric, and how they perform in matric. This, and particularly the achievement of Bachelor passes, explains much of the differences in university outcomes by race, gender and province.
Keywords: I21; I23; I24; 330; higher education; university access; post-school transitions